KEBIJAKAN DAN MODEL PEMBIAYAAN MADRASAH DALAM MENINGKATKAN MUTU PENDIDIKAN ISLAM DI INDONESIA - Jemani, Abdurahman (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2023)
The implementation of quality and quality education is a valuable investment. Education funding has a very important role in the educational process, financing in the world of education is a supporting factor for the implementation of quality education which is contained in financing policies. The type of research used is library research, which is a series of activities related to library data collection methods originating from books, magazines, documents, records of historical stories or pure literature research related to the object of research. Educational policies that support the continuity of the implementation of education in Indonesia are urgently needed in efforts to realize quality education so as to produce graduates who are superior and quality generations of the nation.